Building eConsult (Electronic Consults) Capability at an Academic Medical Center to Improve Efficiencies in Delivering Specialty Care - Matthew A. Thompson; Anne L. Fuhlbrigge; Duane W. Pearson; David R. Saxon; Linda A. Oberst-Walsh; John F. Thomas (SAGE Publishing, 2021)
As the COVID-19 health crisis continues to reshape healthcare, systems across the country face increasing pressure to adapt their models of care to expand access to care, while also improving efficiency and quality in the face of limited resources. Consequently, many have shown a growing interest and receptivity to the expansion of telehealth models to help meet these demands. Electronic consultations (eConsults) are a telehealth modality that allow for a non-face-to-face asynchronous consultation between a primary care provider (PCP) and a specialist aimed at facilitating specialist input without the need for a patient visit. The aim of this case study is to describe eConsults, how they differ from traditional in person models of care and other models of telemedicine and to review the evidence related to the effectiveness of eConsults by PCPs and clinicians from multiple specialties at the University of Colorado School of Medicine. We have worked to develop an infrastructure, delivery system integration, and care model adaptations that aim to improve delivery system performance by ensuring proper care in appropriate settings and lowering costs through reduced utilization. Lastly, we have increased care coordination, improved collaboration and better care transitions through strengthening of relationships between community-based PCPs and academic medical center-based specialists. This work has resulted in cost savings to patients and positive provider satisfaction.